Technology Integration in Arabic Language Curriculum from a TPACK Perspective: A Case Study in an Islamic State High School - Putra, Harfi Ade Febra; Aziz, Mahbub Humaidi; Asy’arie, Bima Fandi; Hidayatullah, Moh Iqbal Dwi; Syihab, M. Alwi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to identify technology integration in the curriculum and analyze the Arabic language learning process within the TPACK framework. This research method uses a qualitative approach with a case study design, based on in-depth interviews with 21 informants, which are then strengthened by field observations and document analysis. The study was conducted at Madrasah Aliyah Negeri (MAN) 2, Malang City, Indonesia. The research results show that technology integration in the curriculum strengthens three main dimensions: learning planning, material management, and learning evaluation. Technology helps develop modules, map objectives, coordinate teachers, organize materials, update learning resources, and accelerate assignments, assessments, and feedback. The findings also demonstrate the use of digital platforms such as LMS and Edu-Panda, the Digital Madrasah Report, and the institutional commitment to the Digital Madrasah policy. In Arabic language learning, the TPACK framework illustrates the integration of content mastery, pedagogical strategies, and technology utilization in the delivery of materials, classroom interactions, and assignment management. The study emphasizes that technology integration is not only technical but also curricular, pedagogical, and institutional. The implications of this study emphasize the need for madrasas to strengthen teachers’ competencies and continuously optimize their digital platforms to support current developments.